The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1158/0008-5472.can-04-2033
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin in Prostate Cancer Bone Metastasis

Abstract: Osteoprotegerin (OPG), a critical regulator of osteoclastogenesis, is expressed by prostate cancer cells, and OPG levels are increased in patients with prostate cancer bone metastases. The objective of this study was to investigate the effects of OPG overexpression on prostate cancer cells and prostate cancer/bone cell interactions in vitro and in vivo. OPGtransfected C4-2 cells expressed 8.0 ng OPG per mL per 10 6 cells, whereas no OPG was detected in the media of C4-2 cells transfected with a control plasmid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 26 publications
(42 reference statements)
2
71
1
2
Order By: Relevance
“…Thus, RANK expressed on both osteoclasts and prostate cancer cells in tumoral bone microenvironment has a propensity for prostate cancer bone metastasis development by synergic effect. Indeed, despite its overall osteoblastic profile, recent evidences suggested the significant involvement of osteolytic lesion preceding osteoblastic prostate cancer bone metastasis development [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, RANK expressed on both osteoclasts and prostate cancer cells in tumoral bone microenvironment has a propensity for prostate cancer bone metastasis development by synergic effect. Indeed, despite its overall osteoblastic profile, recent evidences suggested the significant involvement of osteolytic lesion preceding osteoblastic prostate cancer bone metastasis development [4][5][6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that OPG expression by prostate cancer cells [8] and more recently RANK expression by cancer cells [21,22], these all findings therefore led us to elucidate the molecular mechanisms underlying prostate cancer bone metastases and the therapeutic relevance of RANKL/RANK/OPG triad in these processes, using DU145 and PC3 human prostate cancer cell lines.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Four-to 6-week-old male SCID mice (Fox Chase SCID mice, Charles River, Wilmington, MA) were injected with approximately 2 × 10 5 cells into the proximal end of the right tibia as we have described previously [33][34][35]. Tumor growth was monitored by serum levels of prostate specific antigen (PSA).…”
Section: Intra-tibial Tumorsmentioning
confidence: 99%